Factors Influencing Talent Retention in Malaysia’s Semiconductor Industry - Soon, Shi Wen; Bhardwaj, Rajeev; Qazi, Sayeeduz Zafar; Senathirajah, Abdul Rahman Bin S; Haque, Rasheedul; Krishnasamy, Hariharan N (Journal of Ecohumanism, 2025)
The main objective of this study is to examine the underlying factors that influence talent retention in Malaysia's semiconductor industry. Utilizing Maslow's Hierarchy of Needs and Herzberg’s Two-Factor Theory, the research assesses the impact of employee engagement, career development, reward management, and work-life balance on retaining talent within this sector. A quantitative approach was employed, gathering data through online questionnaires distributed to senior executives in the semiconductor industry. Using purposive sampling, a total of 431 questionnaires were collected via an online platform for convenience. The study's findings reveal that talent retention in Malaysia’s semiconductor industry is significantly influenced by factors such as employee career development, reward management, and work-life balance. These insights offer valuable implications for the industry, highlighting the crucial role these factors play in retaining talent. Given the pivotal role of Malaysia's semiconductor industry in both the national economy and the global market, the study's findings are of considerable importance. The research discusses both practical and theoretical implications, providing recommendations for industry practices and suggesting areas for future research to further understand and improve talent retention strategies.